Transfusion-Dependent Anemia in a Simultaneous Pancreas and Kidney Transplant Recipient - Jeevan Prakash Gopal; David Taube; John Martin; Simona Deplano; Saral Desai; Vassilios Papalois; Anand Sivaprakash Rathnasamy Muthusamy (Case Reports in Transplantation)
A case of transfusion-dependent anemia in a simultaneous pancreas and kidney (SPK) transplant recipient that masqueraded as gastrointestinal bleeding (GIB) is described. The anemia was attributed to bleeding from the donor duodenal cuff based on balloon enteroscopy findings. The patient underwent multiple contrast-enhanced computed tomography scans and multiple endoscopies with confounding features until, eventually, the diagnosis was established. We discuss the diagnostic difficulties and the therapeutic dilemma, along with the pitfalls in ascertaining the final diagnosis.